A novel P38α MAPK activator Bruceine A exhibits potent anti-pancreatic cancer activity - Cai Lu; Lu Fan; Peng-Fei Zhang; Wei-Wei Tao; Cheng-Bin Yang; Er-Xin Shang; Fei-Yan Chen; Chun-Tao Che; Hai-Bo Cheng; Jin-Ao Duan; Ming Zhao (Computational and Structural Biotechnology Journal, 2021)
Pancreatic cancer remains one of the cancers with the poorest prognosis bearing an overall 5-year survival rate of about 5%. Efficient new chemotherapic drugs are still highly desired. Here, bruceine A, a quassinoid identified from the dried fruits of Brucea javanica (L.) Merr., displayed the most potent anti-proliferation activity against pancreatic cancer in vitro and in vivo. Phosphoproteomic analysis revealed p38α MAPK phosphorylation was involved in bruceine A’s action in MIA PaCa-2 cells. Utilizing fortebio octet system and microscale thermophoresis, we found p38α MAPK had high affinity for bruceine A. Molecular docking and molecular dynamic simulations showed that bruceine A widely bound to residues (Leu171, Ala172, Met179, Thr180, Val183) in P-loop of p38α MAPK. Key determinants of bruceine A binding with P-loop of p38α MAPK were 19-CO, 22-CH3, 32-CH3, and 34-CH3. Taken together, our findings demonstrate that bruceine A binds directly to p38α MAPK, which can be used to probe the role of p38α MAPK phosphorylation in pancreatic cancer progression, and as a novel lead compound for pancreatic cancer therapy.